Yeast-Host Interactions: Anadenanthera colubrina Modulates Virulence Factors of C. albicans and Inflammatory Response In Vitro - Maia, Carolina Medeiros de Almeida; Pasetto, Silvana; Nonaka, Cassiano Francisco Weege; Costa, Edja Maria Melo de Brito; Murata, Ramiro Mendonça (Frontiers in Pharmacology, 2021)
Oral candidiasis is one of the most common fungal infections in humans. Its incidence has increased widely, as well as the antifungal resistence, demanding for the search for novel antifungal therapeutic agents. Anadenanthera colubrina (Vell.) Brenan is a plant species that has been proven to possess pharmacological effects, including antifungal and anti-inflammatory activities. This study evaluated in vitro the effects of standardized A. colubrina extract on virulence factors of C. albicans and its regulation on immune response through C. albicans-host interaction. Antifungal activity was evaluated by Broth Microdilution Method against reference Candida strains (C. albicans, C. glabrata, C. tropicalis; C. dubliniensis). Anti-biofilm effect was performed on C. albicans mature biofilm and quantified by CFU/mL/g of biofilm dry weight. Proleotlytic enzymatic activities of proteinase and phospholipase were assessed by Azocasein and Phosphatidylcholine assays, respectively. Cytotoxicity effect was determined by Cell Titer Blue Viability Assay on Human Gingival Fibroblasts. Co-cultured model was used to analyze C. albicans coexisting with HGF by SEM and fluorescence microscopies; gene expression was assessed by RT-PCR of C. albicans enzymes (SAP-1, PLB-1) and of host inflammatory cytokines (IL-6, IL-8, IL-1β, IL-10). Cytokines secretion was analysed by Luminex. The extract presented antifungal effect with MIC<15.62 µg/mL against Candida strains. Biofilm and proteolytic activity were significant reduced at 312.4 µg/mL (20 x 15.62 µg/mL) extract concentration. Cell viability was maintained higher than 70% in concentrations up to 250 µg/mL (LD50=423.3 µg/mL). Co-culture microscopies demonstrated a substantial decreased in C. albicans growth and minimal toxicity against host cells. Gene expressions of SAP-1/PLB-1 were significantly down-regulated and host immune response was modulated by a significant decreased on IL-6 and IL-8 cytokines secretion. A. colubrina had antifungal activity on Candida strains, antibiofilm and anti-proteolytic enzyme effects against C. albicans. Presented low cytotoxicity to the host cells and modulatory effects on the host immune response.